Le regard de Sebastião Salgado sur les -travailleurs de la mine de Serra Pelada (1986) : esthétique d’une servitude moderne - Marion Gautreau (Caravelle)
In this article we study one of the famous reports of the Brazilian photographer Sebastião Salgado: “The gold mine of Serra Pelada. State of Pará. Brazil”. Made in 1986, these photographs belong to a bigger project called “man’s hand”, aiming to represent different ways of working in our planet. The report about the gold mine interrogates the relation between man and profit, the border between humanity and animality, including the persistence of relations of domination in Latin America at the end of the 20th century.